2021
DOI: 10.3390/app11041430
|View full text |Cite
|
Sign up to set email alerts
|

Speech Intelligibility Analysis and Approximation to Room Parameters through the Internet of Things

Abstract: In recent years, Wireless Acoustic Sensor Networks (WASN) have been widely applied to different acoustic fields in outdoor and indoor environments. Most of these applications are oriented to locate or identify sources and measure specific features of the environment involved. In this paper, we study the application of a WASN for room acoustic measurements. To evaluate the acoustic characteristics, a set of Raspberry Pi 3 (RPi) has been used. One is used to play different acoustic signals and four are used to r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…These studies demonstrated that the SSL based on DNNs significantly improved the accuracy and robustness of the model compared with traditional signal processing-based methods. Furthermore, [12] used a CNN to analyze the speech intelligibility, which shows the suitability of a CNN for processing acoustic data. The microphone array-based sound localization method can be implemented using an analytic sound source localization (SSL) algorithm such as in [4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies demonstrated that the SSL based on DNNs significantly improved the accuracy and robustness of the model compared with traditional signal processing-based methods. Furthermore, [12] used a CNN to analyze the speech intelligibility, which shows the suitability of a CNN for processing acoustic data. The microphone array-based sound localization method can be implemented using an analytic sound source localization (SSL) algorithm such as in [4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…These studies demonstrated that the SSL based on DNNs significantly improved the accuracy and robustness of the model compared with traditional signal processing-based methods. Furthermore, [12] used a CNN to analyze the speech intelligibility, which shows the suitability of a CNN for processing acoustic data.…”
Section: Introductionmentioning
confidence: 99%